The STRATEGI BADAN PUSAT STATISTIK KEPULAUAN RIAU DALAM PEMBINAAN STATISTIK SEKTORAL DI KEPULAUAN RIAU: Analisis Strategi Pembinaan Statistik Sektoral BPS Kepulauan Riau Berdasarkan Teori Good Governance - Afrizal; kamarullah, nugraha; Crysanda Putri, Bunga (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2025)
Sectoral statistical development refers to the capacity to analyze and evaluate statistical data that is essential for decision-making across various sectors. The issuance of Presidential Regulation No. 39 of 2019 has encouraged active collaboration between Statistics Indonesia (BPS) and Regional Government Institutions to meet data needs in accordance with standardized principles under the One Data Indonesia (SDI) initiative. This study examines the strategies implemented by BPS of the Riau Islands Province in sectoral statistical development, in its role as the coordinator of the One Data Indonesia program. This research employs a qualitative approach, utilizing primary data collected through interviews and secondary data from literature reviews. The evaluation results of the Sectoral Statistics Implementation (EPSS) indicate that the Riau Islands Province achieved a 'Good' rating, with a significantly improved Statistical Development Index (IPS) score in 2024 compared to 2023. The findings demonstrate that the sectoral development strategies implemented by BPS Riau Islands reflect the principles of Good Governance, as evidenced by the realization of transparency, accountability, participation, effectiveness, and excellent public service